2022
DOI: 10.2807/1560-7917.es.2022.27.35.2200636
|View full text |Cite
|
Sign up to set email alerts
|

Monkeypox DNA levels correlate with virus infectivity in clinical samples, Israel, 2022

Abstract: The current monkeypox virus global spread and lack of data regarding clinical specimens’ infectivity call for examining virus infectivity, and whether this correlates with results from PCR, the available diagnostic tool. We show strong correlation between viral DNA amount in clinical specimens and virus infectivity toward BSC-1 cell line. Moreover, we define a PCR threshold value (Cq ≥ 35, ≤ 4,300 DNA copies/mL), corresponding to negative viral cultures, which may assist risk-assessment and decision-making reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
39
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 11 publications
3
39
0
Order By: Relevance
“…Replication-competent MPXV isolated from skin lesion swabs, oropharyngeal swabs, anal swabs, urethral swabs, and semen has been reported previously (5,(7)(8)(9)(10)(11). However, MPXV isolation using oropharyngeal or nasopharyngeal swabs was rarely reported (12)(13). Interestingly, even in the absence of oral lesions in the patient, replication-competent MPXV was also isolated from the oropharyngeal swabs in the study.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Replication-competent MPXV isolated from skin lesion swabs, oropharyngeal swabs, anal swabs, urethral swabs, and semen has been reported previously (5,(7)(8)(9)(10)(11). However, MPXV isolation using oropharyngeal or nasopharyngeal swabs was rarely reported (12)(13). Interestingly, even in the absence of oral lesions in the patient, replication-competent MPXV was also isolated from the oropharyngeal swabs in the study.…”
Section: Discussionsupporting
confidence: 63%
“…Current knowledge is limited to MPXV shedding and the correlation between the detected Ct value and infectious MPXV load in clinical specimens. A previous report indicated that MPXV DNA levels correlated with infectivity in clinical samples and defined a threshold (Ct ≥35; viral DNA ≤4,300 copies/mL) that predicts poorly infectious specimens ( 14 ). The study measured the infectious potential of the first passages of virus isolation, with a Ct value of 20.76 for the skin blister fluid swab, the infectious MPXV was 6 × 10 4 PFU/mL.…”
Section: Discussionmentioning
confidence: 99%
“… 1 Viral load in the anal swab of the patient (PCR cycle threshold 26·8) was consistent with the presence of replication-competent virus. 4 Moreover, monkeypox virus isolation from a urethral swab of an asymptomatic patient was reported, supporting contagiousness of asymptomatically infected people via sexual contacts. 3 Therefore, our case could probably transmit the infection.…”
mentioning
confidence: 93%
“…(accessed on 1 September 2022). Limited information is available on the relationship of the infectious viral load observed in samples vs. the dose we used in our experiment [ 9 , 10 ]. However, information is available on the Ct values of human samples, and the highest viral load is observed in samples obtained from lesions, with Ct values around 12–16, the Ct value of the virus used for inactivation was 9, suggesting that the viral load we used is higher than what is typically observed in human lesion samples.…”
Section: Resultsmentioning
confidence: 99%
“…While it is postulated that MPXV viral loads are higher in skin lesions than in pharyngeal swabs, these are extrapolated from Ct values obtained when samples were tested by PCR [ 12 ]. There are limited studies showing correlation between Ct value and MPXV viral load in clinical material and these show that the Ct values over 33 have viral copy numbers near the limit of detection (25 pfu/mL) [ 10 ]. Previous animal studies also have shown that culture is successful in lesions with viral load of 10 4 to 10 5 copies/mL [ 13 ].…”
Section: Resultsmentioning
confidence: 99%